Retrospective Case Study on the Evaluation of Inflammatory Markers, Macrophage Inhibitory Protein-1α and Interferon-γ in Sleep Deprivation Condition - Visallini T.S (Wolters Kluwer Medknow Publications, 2024)
Background and AimSleep is an important physiological process that is necessary for the normal functioning of the body. Sleep greatly affects all aspects of our body, including the immune pathways or immune response system of our body, which plays a determinant role in the development and progression of chronic inflammatory diseases. In this study, we worked to find the relation between sleep deprivation and levels of pro-inflammatory markers macrophage inflammatory protein 1-alpha (MIP-1α) and interferon gamma (IFN-γ). To find the relation between sleep deprivation and levels of pro-inflammatory markers MIP-1α and IFN-γ. ObjectiveTo find the relation between sleep deprivation and levels of pro-inflammatory markers MIP-1α and IFN-γ. Materials and MethodsThe study was conducted with 40 individuals as participants, of which 20 were sleep-deprived (SD), and 20 had adequate amounts of sleep. The sleep duration details of the individuals were obtained by questionnaire. Blood was withdrawn from all the subjects after due consent from them. Plasma was separated and was used to evaluate their MIP-1α levels and IFN-γ levels. ResultsThe MIP-1α levels and levels of IFN-γ were found to be significantly elevated in the SD individuals than that of individuals who had adequate sleep. ConclusionSleep loss and sleep deprivation are associated with altered expressions of key regulatory factors and upregulation of pro-inflammatory cytokines production. Thus, sleep deprivation can be considered to be one of the major contributors to the development and progression of various chronic inflammatory diseases.